How female principals in Ethiopia fight for gender justice: a qualitative study of their challenges and strategies - Alemu, Aklilu (Frontiers in Education, 2024)
Introduction: Recently, women have been taking leadership positions in the hope of reducing gender inequality. However, it is unclear whether these female leaders have made a significant contribution to closing the gender gap. Guided by social role theory, this research explored the roles of female principals in reducing gender inequality in primary schools.The study used a multisite case study design. Data were collected from 39 respondents: female directors, male and female students, and male and female teachers. Focus group discussions and interviews were the tools for gathering relevant data. The study utilized a six-staged thematic analysis approach with the help of NVivo 11 versions of qualitative analysis software.The study revealed that, besides being role models and counselors to female students, the role of female directors in minimizing gender inequality was insufficient due to the deeply entrenched traditional discrimination against women.Discussion: Gender inequality in education stems from social roles, and female principals are assumed to help avoid or minimize gender disparity in a male-dominated world. However, achieving gender equality requires the collective efforts of parents, principals, society, and the government.Future quantitative or mixed-method research is important to determine the extent to which female principals have contributed to reducing gender inequality.